1995
DOI: 10.1007/bf01690261
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered resistance to potato virus X in four commercial potato cultivars

Abstract: The genes for the capsid protein (CP) and the 8K movement protein of PVX were introduced into potato (Solanum tuberosum L.) and expressed under the control of CaMV 35S promoter using a binary vector andAgrobacterium tumefaciens. Four commercial potato cultivars (Russet Burbank, Shepody, Desirée and Bintje) have been efficiently transformed. Eleven independent transgenic clones, with CP expression levels higher than 0.05% of the soluble leaf proteins, were analyzed for resistance to inoculation with PVX (5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, there are fewer examples where such sequences of potato virus genomes have been incorporated into the potato genome and have been shown to confer resistance to those viruses. Nevertheless, this has been accomplished with sequences derived from PLRV (Barker et al, 1992;Brown et al, 1995;Ehrenfeld et al, 2004;Graham et al, 1997;Kawchuk et al, 1997;Kawchuk et al, 1990;Murray et al, 2002;Palucha et al, 1998;Rovere et al, 2001;Thomas et al, 2000), PVY (Chi et al, 2005;Hefferon et al, 1997;MakiValkama et al, 2001;Malnøe et al, 1994;Missiou et al, 2004;Okamoto et al, 1996;Racman et al, 2001;Schubert et al, 2004;Smith et al, 1995;Sokolova et al, 1994;Wefels et al, 1993), PVA (Nie et al, 2008), both PLRV and PVY (Arif et al, 2009), PVX (Doreste et al, 2002Hoekema et al, 1989;Spillane et al, 1998;Xu et al, 1995), both PVX and PVY (Lawson et al, 1990), PMTV (Germundson et al, 2002;Melander et al, 2001), TRV (Melander, 2006) and PSTVd (Matousek et al, 1994;Yang et al, 1997). Solomon-Blackburn and Barker (2001a) have suggested that transgenic resistance derived by stacking sequences from several viruses may offer to best means of obtaining multiple virus resistance, given that the sources of host-derived resistance to the various potato viruses involve different breeding lines and even different Solanum species.…”
Section: Transgenic Resistancementioning
confidence: 99%
“…However, there are fewer examples where such sequences of potato virus genomes have been incorporated into the potato genome and have been shown to confer resistance to those viruses. Nevertheless, this has been accomplished with sequences derived from PLRV (Barker et al, 1992;Brown et al, 1995;Ehrenfeld et al, 2004;Graham et al, 1997;Kawchuk et al, 1997;Kawchuk et al, 1990;Murray et al, 2002;Palucha et al, 1998;Rovere et al, 2001;Thomas et al, 2000), PVY (Chi et al, 2005;Hefferon et al, 1997;MakiValkama et al, 2001;Malnøe et al, 1994;Missiou et al, 2004;Okamoto et al, 1996;Racman et al, 2001;Schubert et al, 2004;Smith et al, 1995;Sokolova et al, 1994;Wefels et al, 1993), PVA (Nie et al, 2008), both PLRV and PVY (Arif et al, 2009), PVX (Doreste et al, 2002Hoekema et al, 1989;Spillane et al, 1998;Xu et al, 1995), both PVX and PVY (Lawson et al, 1990), PMTV (Germundson et al, 2002;Melander et al, 2001), TRV (Melander, 2006) and PSTVd (Matousek et al, 1994;Yang et al, 1997). Solomon-Blackburn and Barker (2001a) have suggested that transgenic resistance derived by stacking sequences from several viruses may offer to best means of obtaining multiple virus resistance, given that the sources of host-derived resistance to the various potato viruses involve different breeding lines and even different Solanum species.…”
Section: Transgenic Resistancementioning
confidence: 99%